Hydrogen peroxide production in a pilot-scale microbial electrolysis cell - Sim, Junyoung (2018)
A pilot-scale dual-chamber microbial electrolysis cell (MEC) equipped with a carbon gas-diffusion cathode was evaluated for H2O2 production using acetate medium as the electron donor. To assess the effect of cathodic pH on H2O2 yield, the MEC was tested with an anion exchange membrane (AEM) and a cation exchange membrane (CEM), respectively. The maximum current density reached 0.94–0.96 A/m2 in the MEC at applied voltage of 0.35–1.9 V, regardless of membranes. The highest H2O2 conversion efficiency was only 7.2 ± 0.09% for the CEM-MEC. This low conversion would be due to further H2O2 reduction to H2O on the cathode or H2O2 decomposition in bulk liquid. This low H2O2 conversion indicates that large-scale MECs are not ideal for production of concentrated H2O2 but could be useful for a sustainable in-situ oxidation process in wastewater treatment.